2022
DOI: 10.1093/crocol/otac021
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Suboptimal Treatment and Associated Healthcare Costs Among Patients With Crohn’s Disease Initiated on Biologic or Conventional Agents

Abstract: Background As the treatment landscape for Crohn’s disease (CD) evolves, an up-to-date understanding of the burden associated with indicators of suboptimal treatment is needed. The aim of this study was todescribe suboptimal treatment indicators and associated healthcare costs among CD patients initiated on a biologic or conventional agent. Methods Adults with CD were identified in a US healthcare claims database (Optum’s Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 12 , 14 , 26 , 27 In this study, over 70% of patients were persistent to ustekinumab at 12 months, suggesting that some level of disease control was achieved for a substantial proportion of patients with UC reaching maintenance in the studied population. Persistence on a biologic may present additional advantages to the health system and to patients, as restart and switch can be interpreted as indicators of suboptimal treatment, which were found to be associated with higher healthcare costs 28 and reduced quality of life 25 among patients with IBD. The latter is an especially important consideration, given that in addition to improving clinical outcomes, a major goal of the treat-to-target strategy for IBD is to restore patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 14 , 26 , 27 In this study, over 70% of patients were persistent to ustekinumab at 12 months, suggesting that some level of disease control was achieved for a substantial proportion of patients with UC reaching maintenance in the studied population. Persistence on a biologic may present additional advantages to the health system and to patients, as restart and switch can be interpreted as indicators of suboptimal treatment, which were found to be associated with higher healthcare costs 28 and reduced quality of life 25 among patients with IBD. The latter is an especially important consideration, given that in addition to improving clinical outcomes, a major goal of the treat-to-target strategy for IBD is to restore patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Event costs were derived from a recently published claim‐based analysis 34 . This study identified cohorts of patients with CD initiated on either a biologic or conventional agent and reported incremental per patient per year cost estimates for multiple suboptimal treatment indicators; several of these indicators matched clinical events that occurred in our model.…”
Section: Methodsmentioning
confidence: 99%
“…33 Event costs were derived from a recently published claim-based analysis. 34 This study identified cohorts of patients with CD initiated on either a biologic or conventional agent and reported incremental per patient per year cost estimates for multiple suboptimal treatment indicators; several of these indicators matched clinical events that occurred in our model. Based on expert recommendation and to reflect the real-world costs of suboptimal CD treatment more accurately, we parameterized incremental medical costs (i.e., inpatient, emergency department, outpatient, and other costs) over the subsequent year for biologic patients that experienced surgery, switched biologics, or switched to CT, and CT patients that experienced surgery (Event Cost Calculations in Data S1).…”
Section: Costsmentioning
confidence: 99%
“…Precision-Guided Dosing on Management of Patients With IBD inadequate induction) with mean PMPY costs ranging from $46,100 (no indicator) to $68,572 (≥ 4 indicators). 10 A useful approach to biologic optimization in IBD is therapeutic drug monitoring (TDM), which involves assessing serum levels of drug and anti-drug antibodies to guide dosing decisions and to improve the probability of sustained remission. Compared with empiric changes in dosing that have been shown to lack correlation with disease activity, 11 TDM is considered to be both the standard of care and more advantageous.…”
Section: Real-world Impact Of Infliximabmentioning
confidence: 99%